Quantifying the Contribution of Public Parks to Physical Activity and Health Introducing SOPARC - Cohen, Deborah A. (RAND Corporation, 2014)
This paper introduces the System for Observing Play and Recreation in Communities (SOPARC), a reliable, valid, and easy-to-use tool for quantifying park use and park-based physical activity. The authors explain what SOPARC is and how it is used, as well as provide background information on the importance of physical activity to health.